Engineering the porosity and acidity of H-Beta zeolite by dealumination for the production of 2-ethylanthraquinone via 2-(4′-ethylbenzoyl)benzoic acid dehydration. Issue 18 (8th March 2018) - Liu, J. X.; He, N.; Liu, C. Y.; Wang, G. R.; Xin, Q.; Guo, H. C.
Abstract : Mild HNO3 treated nano-sized H-Beta zeolite showed outstanding catalytic activity, selectivity and reusability, compared with a commercial oleum catalyst. Abstract : Environmentally-friendly zeolites have been used commercially to replace concentrated sulfuric acid and oleum in the alkylation reactions and dehydration of alcohols. However, moderate activity, associated with access and diffusion limitations, low intramolecular dehydration selectivity, associated with unsatisfactory acidity, and unknown reusability have hampered their industrial implementation in the dehydration of bulky 2-(4′-ethylbenzoyl)benzoic acid (E-BBA) to 2-ethylanthraquinone (2-EAQ). Herein, we have discovered that after being treated with mild HNO3, nano-sized H-Beta zeolite showed outstanding catalytic activity, selectivity and reusability, compared with a commercial oleum catalyst. A number of techniques, such as XRD, XPS, XRF, 29 Si MAS NMR, 27 Al MQ MAS NMR, FTIR, NH3 -TPD, argon physisorption and HR-TEM, have been employed to decouple the interdependence between acidity, porosity and catalytic performance. It was found that mild HNO3 treatment could clean out the extra-framework aluminium deposits and selectively extract the aluminium species on the outer surface of Beta zeolites, which strengthened the acidity of the Brønsted acid sites (Si(OH)Al) inside the H-Beta micropores, thus increasing the possibility of intramolecular dehydration of E-BBA. Moreover, this mild HNO3 treatment also dredged the network of intercrystalline mesopores, alleviating the diffusion constraints. Therefore, through the dual adjustment of acidity and porosity, dealuminated H-Beta zeolite has a promising future in the green synthesis of 2-EAQ.